2015
DOI: 10.1186/s12868-015-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor interacting protein 3-induced RGC-5 cell necroptosis following oxygen glucose deprivation

Abstract: BackgroundNecroptosis is a type of regulated form of cell death that has been implicated in the pathogenesis of various diseases. Receptor-interacting protein 3 (RIP3), a member of the RIP family of proteins, has been reported as an important necroptotic pathway mediator in regulating a variety of human diseases, such as myocardial ischemia, inflammatory bowel disease, and ischemic brain injury. Our previous study showed that RIP3 was expressed in rat retinal ganglion cells (RGCs), where it was significantly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Studies have revealed that necroptosis contributed to the selective and delayed death of certain populations of neurons that occurs following an ischemic stroke 8 , which can be caused by a lack of blood supply to the brain 9 . Necroptosis has also been implicated in ischemic necrosis of retinal cells in several studies 10 12 . Oxygen-glucose deprivation (OGD), an in vitro model of cerebral ischemia, can also induce the death receptor (DR)-dependent component of necroptotic cell death in cultured neurons 13 – 15 , concomitant with the increase in RIPK3/RIPK1 mRNA and protein levels 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that necroptosis contributed to the selective and delayed death of certain populations of neurons that occurs following an ischemic stroke 8 , which can be caused by a lack of blood supply to the brain 9 . Necroptosis has also been implicated in ischemic necrosis of retinal cells in several studies 10 12 . Oxygen-glucose deprivation (OGD), an in vitro model of cerebral ischemia, can also induce the death receptor (DR)-dependent component of necroptotic cell death in cultured neurons 13 – 15 , concomitant with the increase in RIPK3/RIPK1 mRNA and protein levels 16 .…”
Section: Introductionmentioning
confidence: 99%
“…28 According to the manufacturer's protocol (Roche, Mannheim, Germany), we detected cell apoptosis via TUNEL staining. The brain was removed and frozen in liquid nitrogen and then stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The RGC-5 cell line was provided by the Department of Ophthalmology, Second Hospital of Jilin University in China ( Ding et al, 2015 ). RGC-5 cells were cultured in DMEM (Thermo Scientific) supplemented with 10% FBS (Thermo Scientific) and 1% Penicillin-Streptomycin (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%